2020
DOI: 10.31234/osf.io/fzwgs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting group benefits in joint multiple object tracking

Abstract: In daily life, humans often perform visual tasks together such as, for instance, solving puzzles or looking for a misplaced key. In such tasks, humans tend to distribute task demands, enabling them to reach a higher performance compared to performing the same task alone – a group benefit. Research on group benefits in joint visual tasks has found that the availability of performance feedback and information about each other’s actions are two important factors influencing group benefits. Yet, no study has syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…These results also suggest that the description of an artificial partner does not only alter how participants co-represent the task of an artificial partner in a joint stimulus-response compatibility task (Stenzel et al, 2012) but critically, it affects humans' willingness to share task load in a joint visuospatial task. Moreover, our findings suggest that the left / right labour division that has been preferred by human-human pairs across several studies Wahn and Kingstone, 2020;Wahn et al, 2020b) is also readily adopted when humans and a computer partner share task load.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…These results also suggest that the description of an artificial partner does not only alter how participants co-represent the task of an artificial partner in a joint stimulus-response compatibility task (Stenzel et al, 2012) but critically, it affects humans' willingness to share task load in a joint visuospatial task. Moreover, our findings suggest that the left / right labour division that has been preferred by human-human pairs across several studies Wahn and Kingstone, 2020;Wahn et al, 2020b) is also readily adopted when humans and a computer partner share task load.…”
Section: Discussionmentioning
confidence: 59%
“…The 64 participants were evenly split across our four conditions. We chose 16 participants as our sample size for each condition to match the statistical power to our earlier study, in which we collected 16 pairs for each condition as well (Wahn et al, , 2020b. We also ran a power analysis (Power: 0.80; alpha = 0.05) using G*Power (Faul et al, 2007) and found that our sample size is sufficient to detect effect sizes smaller (Cohen's d = 0.65) than in our earlier study (all Cohen's d were larger than 0.85) for the same analyses that we perform in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation